Development Of Linkage Mechansim For In-Pipe Robot - Teoh, Chee Haw (Universiti Sains Malaysia, 2018)
Conventionally, the monitoring of pipeline for leakage detection is done by workers and is not done within a day. This process instead is done continuously. As the solution of this problem, in-pipe robot had been invented. This robot is proven to be a better choice as it able to perform better than the workers. The purpose of this project is to design and to fabrication an in-pipe robot which have high mobility in pipe of various size. The design includes the mechanism of how the robot moving (Locomotion), electrical (wiring), the shape or weight of the robot and also the programming. Each of the aspects are essential as it will affect the performance and the efficiency of the robot. The final design of the in-pipe robot is a robot that is attached with a flexible front wheel. This design able to cause the robot to make a turn in the pipe. The robot also comprises of only three 6V motors to moving un the pipe. The kinematic model of the in-pipe robot is driven and the prototype has been developed. The in-pipe robot will able to turn either left or right by controlling the direction of the motor. The performance of the robot will then be verified by experimentation. The robot able to turn in the T-shape pipe by controlling the direction of the motor.